A fairy's gift - Thorpe, Kiki (Thorpe, Kiki. Never girls, 2015)
"When the Never Girls find out that widespread disbelief is threatening the fairies, they have to spend their holiday break finding a way to make their families and neighbors believe in fairies again--and save the magic of Pixie Hollow"--